Shared financial management of Community programs and its implementation in the EU area - Jedličková, Vladislava (2012)
The issue of migration within the European Union has grown in member countries to considerable size. Management representatives of EU institutions have decided to address this situation. They established community program Solidarity and management of migration flows. The European Commission has decided that for the financial management of this program will be used the principle of shared management. The principle of shared financial management is the delegation of powers and responsibilities for funding and implementing the program from the institutions of the European Commission to the Member State. This decision creates an obligation for a Member State to establish a system of financial management programs in accordance with financial rules of the European Union (not by the financial rules of the Member State). So the general program "Solidarity and management of migration flows" became the first community program in the CR, which is being implemented on the principle of shared financial management. Member states are obliged to create their own theoretical and methodological basis of a new financial management. This method of financial management has three pillars - Responsible Authority, Audit Authority and Certification Authority. The recipient of funds may be non-profit organizations or state or public nonprofit organization. The financial management of the Responsible Authority is responsible for program implementation in the Member State through projects of final beneficiaries. The Audit Authority is the control body. The Certification Authority is the authority for confirmation. It is the last link between the European Commission and Member States. The task of the Certification Authority and at the same time of this dissertation was to develop new theoretical and methodological system of internationally recognized certification of public expenditures for services that are financed from the EU budget.